Proofreading & editing precision - Pagel, Larry G. (South-Western Educational Pub., 2001)
This activity-oriented text is designed to sharpen proofreading and editing skills.It provides a thorough review of the rules governing language arts. Computerized exercises found on the data disk are integrated throughout to give the user additional practice in editing and formatting documents just as they would in everyday life. Also included is the Template CD-ROM which provides realistic, hands-on experience in loading, proofreading, editing and formatting stored files. On-screen proofreading is another skill that must be learned and practiced because it is an activity that is performed by anyone who composes communication on computer. Document files on the template are identified in the student edition with a CD-ROM icon. System requirements: Word 6.0, Word97, WordPerfect 6.1 and Works 3.0 for Windows 95 or Windows NT. Word 6.0 and Works 3.0 for Macintosh